Lawrence of Arabia and the representation of Arab nationalism - Carvalho, Paula Carolina de Andrade (2017)
This article intends analyze the representation of Arab nationalism in the movie Lawrence of Arabia (1962), directed by David Lean, having as theoretical basis the political aspect of representation presented by Edward Said in his book Culture and Imperialism (1993), and its association with the expansion of British and American imperialism. Based on the book Seven Pillars of Wisdom (1922) written by British explorer T.E. Lawrence, the film shows his experiences in the Arab Revolt (1916-1918) against the Turks amidst the First World War (1914-1918), making alliances with the Bedouins from the Arab Peninsula, and his participation on the attacks on Aqaba and Damascus as well as his involvement in the formation of the National Arab Council. The movie also explores Lawrence‟s intern emotional battles regarding his own identity, torn between his native Great Britain and the desert Arabs.